Pengaruh Corporate Governance, Capital Intensity dan Profitabilitas Terhadap Tax Avoidance pada Sektor Pertambangan - Jumriaty Jusman; Firda Nosita (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
The study aims to examine the influence of Corporate Governance, Capital Intensity and Profitability on Tax Avoidance.  The proxy of Corporate governance was audit quality and audit committee, while the profitability factor used is Return on Asset (ROA) and Tax Avoidance by Cash Effective Tax Rate. The sample was chosen by purposive sampling and resulted 21 companies from mining sector listed oin Indonesian Stock Exchange from 2016 to 2018. The data analyzed by using multiple linier regression. The result showed that audit quality, audit committee, and capital intensity have insignificant influence on tax avoidance. While ROA has negative significant on tax avoidance